Al2O3/TiO2 double layer anti‐reflection coating film for crystalline silicon solar cells formed by spray pyrolysis. Issue 4 (10th June 2016) - Kanda, Hiroyuki; Uzum, Abdullah; Harano, Norihisa; Yoshinaga, Seiya; Ishikawa, Yasuaki; Uraoka, Yukiharu; Fukui, Hidehito; Harada, Tomitaro; Ito, Seigo
Abstract: An Al2 O3 /TiO2 double layer anti‐reflection coating (ARC) film formed by spray pyrolysis was introduced for monocrystalline silicon solar cells as the nonvacuum processing method. The thickness of the Al2 O3 layer and TiO2 compact layer was controlled by the volume of deposited precursor solution and confirmed by ellipsometry and scanning electron microscopy. The average photovoltaic properties of photocurrent density ( J sc ), open‐circuit photovoltage ( V oc ), fill factor ( FF ), and photo energy conversion efficiency ( η ) were 37.0 mA/cm 2, 590 mV, 0.712, and 15.5%, respectively. A significant improvement on J sc and η could be confirmed owing to the Al2 O3 /TiO2 ARC. The results of Fourier transform infrared (FTIR) spectroscopy and optical simulation with modeling for the reflectance properties confirmed that C‐H‐based organics remained after the deposition of thin films. Abstract : Al2 O3 /TiO2 double layer anti‐reflection coating film formed by spray pyrolysis was introduced for monocrystalline silicon solar cells as a nonvacuum processing method. According to the results of Fourier transform infrared spectroscopy and optical simulation with modeling for the reflectance properties, it was confirmed that C‐H‐based organics remained after the deposition of thin films.